Performance Targets and Ex Post Incentive Plan Adjustments† - Hyun, Jeong‐Hoon; MatĚjka, Michal; (Seung Hwan) Oh, Peter; Ahn, Tae Sik (Contemporary Accounting Research, 2022)
ABSTRACT Performance evaluations are typically based on a formula that specifies in advance all performance measures, their relative incentive weights, and targets to be met. However, beginning‐of‐year performance targets can become outdated due to unforeseen events that call for ex post adjustments to formula‐based incentive plans to restore incentives. We discuss three types of ex post incentive plan adjustments—end‐of‐year subjective performance evaluation, changes in next‐year relative incentive weights, and changes in next‐year performance targets—and empirically examine the extent to which they are used to discourage failure to meet a target by a wide margin. Specifically, we use 2004–2015 data on formula‐based bonus plans, subjective performance evaluations, and performance in Korean state‐owned enterprises. Consistent with our predictions, we find that very low performance relative to target is associated with (i) low subjective evaluations and (ii) an increase in next‐year incentive weights, conditions that render areas with poor performance more important in future evaluations. These findings are more pronounced on performance dimensions of high importance and less pronounced when very low performance is due to an adverse uncontrollable shock. Finally, we find evidence that ex post incentive plan adjustments are associated with future performance improvements. Combined, our findings suggest that ex post incentive plan adjustments can be used to strengthen incentives when performance targets get outdated.